Highly Efficient Red-Emitting Bis-Cyclometalated Iridium Complexes - Lai, Po-Ni; Brysacz, Caroline H; Alam, Md Kamrul; Ayoub, Nicholas A; Gray, Thomas G; Bao, Jiming; Teets, Thomas S (Journal of the American Chemical Society, 2018)
Bis-cyclometalated iridium complexes with enhanced phosphorescence quantum yields in the red region of the visible spectrum are described. Here, we demonstrate that incorporating strongly π-donating, nitrogen-containing β-ketoiminate (acNac), β-diketiminate (NacNac), and N,N′-diisopropylbenzamidinate (dipba) ancillary ligands can demonstrably perturb the excited-state kinetics, leading to enhanced photoluminescence quantum yields (ΦPL) for red-emitting compounds. A comprehensive study of the quantum yields and lifetimes for these complexes reveals that for the compounds with the highest quantum yields, the radiative rate constant (k r) is significantly higher than that of related complexes, and contributes substantially to the increase in ΦPL. Experimental and computational evidence is consistent with the notion that an increase in spin–orbit coupling, caused by an enhancement of the metal-to-ligand charge transfer (MLCT) character of the excited state via destabilization of the HOMO, is mainly responsible for the faster radiative rates. One of the compounds was shown to be effective as the emissive dopant in an organic light-emitting diode device.